Recognition of thyroglobulin autoantigenic epitopes by murine T and B cells. - Champion, B R (1987)
We have used a large panel of thyroglobulins (Tg) prepared from a wide range of mammalian species to study the Tg autoantigenic epitopes recognized by populations of monoclonal and polyclonal murine T and B cells. This approach showed the existence of at least six different epitopes; three recognized by T cells (in association with I-Ak on antigen-presenting cells) and three by B cells (monoclonal antibodies). The majority of serum and monoclonal autoantibodies were found to be highly specific for mouse Tg, with some cross-reactive binding to rat Tg. In contrast, T-cell lines/clones and hybridomas recognized cross-reactive epitopes on Tg that were highly conserved throughout most of the mammalian orders. Moreover, two hybrid clones, which showed similar patterns of cross-reactivity, differed in their responsiveness to tryptic digests of human Tg. Thus, autoreactive T and B cells recognize distinct areas of the Tg molecule.